Vittorio Sereni, the «Libera Stampa» Prize, and the Collection Un lungo sonno (inOpera Esercizi di lettura su testi contemporanei, 2025)
The essay offers a study of Sereni’s participation in the «Libera Stampa» prize and aims firstly to contribute to the analysis of the process that led to Sereni’s establishment in the Italian and international literary field in the 1940s and 1950s. Secondly, the focus is placed on the collection Un lungo sonno, which remained unpublished in the configuration presented by Sereni to the jury of the Swiss prize in 1956. Un lungo sonno is analysed in its macro-textual structure and in its connections with other books by Sereni (among them Diario d’Algeria, Gli strumenti umani, Gli immediati dintorni).
Keywords: Sereni; Premi letterari; «Libera Stampa»; Campo letterario; Un lungo sonno